Exogenous insulin autoimmune syndrome: a case report and literature review - Gao, Yingyi; Wang, Nan; Huang, Zhishan; Bai, Ning (Frontiers in Endocrinology, 2026)
Exogenous Insulin Autoimmune Syndrome (EIAS) is a rare hypersensitivity reaction triggered by the administration of exogenous insulin. This reaction induces the production of insulin autoantibodies, leading to various clinical manifestations such as insulin resistance, hyperglycemia, recurrent hypoglycemic episodes, and allergic reactions. Due to limited clinical awareness, EIAS is often misdiagnosed or overlooked. Herein, we present a case of EIAS in a patient with type 2 diabetes mellitus, providing a detailed analysis of its clinical features, laboratory findings, differential diagnoses, therapeutic approaches, and clinical outcomes, supplemented by a literature review. This report aims to enhance clinicians’ diagnostic and therapeutic proficiency in managing this condition.